Can an intervention alter the perception of palliative care services for heart failure patients?. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Edwards, Laura; Hodgson, Aruna; Arya, Sanjay
Abstract : Background: Although the number of palliative care services which will accept patients with heart failure has increased in recent years, little is known currently about heart failure patients' knowledge of palliative care services or the acceptability of these services to them. Aims: The current study aimed to ascertain the perceptions of heart failure patients with regard to palliative care and whether a brief educational intervention similar to those used in Expert Patient Programmes (EPPs) can alter their perception of palliative care services and attitudes towards access to them. Method: Patients diagnosed with NYHA III/IV heart failure attending a nurse specialist-led clinic were asked to participate in the study. The patients were asked to complete a study-specific questionnaire comprising 12 questions. Each comprised a statement with 5 point Likert scale responses (strongly disagree–strongly agree). The researcher then discussed an educational leaflet regarding local palliative care services with each participant. 2 weeks later the participants were asked to return an identical postal questionnaire. For each question, mean change in response was calculated. Results: 36 paired questionnaires were completed. There was a significant change in patient responses to questions regarding knowledge of local palliative care services, the availability of palliative care services for non-cancer patients and collaborative working between services. There was no significant change in patients' anxiety at visiting the local hospice or meeting a palliative care specialist at home or in hospital. Conclusion: The study showed that a brief educational intervention may inform patients with heart failure about palliative care services but does not seem to alter anxiety regarding them. Further work is required to ascertain the basis of these anxieties and strategies to address them in order to ensure equitable access to all.